To express (x-1)^2 as a trinomial in standard form, we expand the square using the formula (a-b)^2 = a^2 - 2ab + b^2. Substituting a = x and b = 1, we get x^2 - 2x + 1.
To express the expression (x-1)^2 as a trinomial in standard form, we need to apply the square of a binomial formula, which is (a - b)^2 = a^2 - 2ab + b^2. In this case, a is x, and b is 1. Substituting these values into the formula, we get:
(x - 1)^2 = x^2 - 2(x)(1) + 1^2
Now, simplify each term:
1. x^2 represents the square of the first term, which is x.
2. 2(x)(1) = 2x, representing twice the product of x and 1.
3. 1^2 = 1, which is the square of the second term, 1.
So, when we simplify the expression further, we have:
(x - 1)^2 = x^2 - 2x + 1
This is the trinomial representation of (x-1)^2 in standard form. It consists of three terms: x^2, -2x, and 1, with each term having a specific coefficient.
#SPJ2
Answer:
x² - 2x + 1
Step-by-step explanation:
We want to express (x - 1)² as a trinomial. In other words, we want to expand this out.
(x - 1)² = (x - 1)(x - 1)
We use FOIL (First, Outer, Inner, Last). The First terms are x and x. Multiply:
x * x = x²
The outer terms are x and -1. Multiply:
x * (-1) = -x
The inner terms are -1 and x; multiply:
(-1) * x = -x
The last terms are -1 and -1; multiply:
(-1) * (-1) = 1
Add all these together:
x² + (-x) + (-x) + 1 = x² - 2x + 1
~ an aesthetics lover
I'll mark you brainliest of you answer correctly.
Answer:
2nd one is the answer..
Answer:
Average speed, s = 0.8 m/s
Step-by-step explanation:
It is given that,
Distance travelled by a basketball, d = 4 meters
Time taken to cover that distance, t = 5 seconds
We have to find the average speed of the basketball. It is defined as the total distance covered by the basketball divided by total time taken. It can be written as :
or
Putting the values of d and t. We get :
s = 0.8 m/s
Hence, the average speed of the basketball is 0.8 m/s
Answer:
76 teenagers went to movies in the past month.
Step-by-step explanation:
The number of teens who went to movie out of every 5 teens = 4
Total teens surveyed = 95
Let, out of 95 teenagers , the teens who went to movie = m
So, the ratio of people who went : who were surveyed = 4: 5
Now, BY THE LAW OF RATIO AND PROPORTIONALITY
or,
So, m = 76
⇒ 76 teenagers went to movies in the past month.